Science and strategic communication: how can universities attract high school students? - Ruão, Teresa (2015)
As the use of new media and the new uses of traditional media evolve in the contemporary This is a study on the use of science communication as a component of the promotional mix prepared by universities to attract high school students to their graduate and postgraduate programmes. It proposes the concept of strategic science communication, to name strategic communication practices that use science popularization to reach successful organizational performance. And this proposal was tested through a survey applied to high school students, within the area of influence of the University of Minho, in Portugal. The survey was designed according to a model of analysis developed to study the ability of strategic science communication to act on awareness (familiarity), enjoyment (appreciation), interest (voluntary involvement), opinion (way of thinking), understanding (comprehension), interaction (contact activities) and action (attitude); by extending Burns et al. (2003, p.191) vowel analogy. In the end, results point out: (1st) to the relevance of strategic communication activities in the process of promoting information and interaction with science; (2nd) to the positive effect of science communication activities in the desire to apply for a higher education institution; and (3rd) to the pertinence of the strategic science communication concept in universities’ communication mix.